Avoiding repetitive mistakes: Understanding post-error adjustment in response to head fake actions - Qian, Y.; Wu, B.; Chen, X.; Chi, L. (Psychology of Sport and Exercise, 2025)
Head fake is a common deceptive action in basketball that can effectively disrupt opponents and induce errors. This study investigated post-error behavioral adjustment and neural changes associated with head-fake action and related action cues across different response-stimulus intervals (RSIs). Participants were asked to respond to the central target player's pass direction, ignoring the head direction of the target person and the flankers. The results revealed that the participants exhibited longer reaction times in the flanker (or head) incongruent condition compared to the flanker (or head) congruent condition. The results also revealed that the participants slowed their responses following an error in response to an action cue, indicating the presence of the post-error slowing (PES) effect. Moreover, the PES effect was greater at short RSI than at long RSI. The results of Event Related Potentials (ERPs) revealed that the participants exhibited a greater amplitude of error-related negativity (ERN) but a smaller amplitude of error positivity (Pe) following an error at a short RSI than at a long RSI. Collectively, these findings suggest that people can exhibit post-error slowing following an error response to action cues. Moreover, the RSI may affect the speed of response after an error and early error processing and erroneous evidence accumulation, as a processing bottleneck exists for a short time after an error. These findings offer insights into sports strategies and behavior modification.